Pembuatan dan Pelatihan Pengelolaan Website Desa di Desa Tapango Kabupaten Polewali Mandar - Reski Wahyu Yanti; Putri Indi Rahayu (Sipakaraya : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to provide training to village officials on how to create and manage websites. Based on survey and interview results, the administrative services provided are still traditional in nature. This is a slow process compared to other villages in the context of rapidly developing technology. Tapango Village residents need faster administrative services via the village website. Village officials' human resources must be immediately strengthened to create and manage this website optimally. The implementation of this community service is carried out through several stages, namely the communication stage, discussing with partners regarding the problems faced, and the next stage is communication with the Head of Tapango Village to explain and ensure that using the website is the right solution, the stage of agreeing on the training schedule, the stage of document design , the preparation stage for implementing training, the implementation stage for website creation and management training as well as the monitoring and evaluation activity stage to measure the success of the training provided. The results obtained from these systematic steps have been able to achieve the PKM objectives as stated above.